ChatGPT’s Healing Words: Navigating the Frontiers of Conversational AI in Healthcare - Hassan Zaidi, Syed Muhammad; Khan, Abdul Hafeez; Hassan, Imtiaz; Naim, Syeda Wajiha (Journal of Information Systems Research and Practice, 2024)
This comprehensive review paper investigates the unique role of ChatGPT in medical healthcare, exploring its effect on patient engagement, clinical support, and healthcare communication by dissecting the strengths and weaknesses of ChatGPT in this domain. It highlights the potential to enhance patient care, streamlining administrative tasks to foster a more accessible healthcare experience. The paper navigates through real-world applications, shedding light on successful implementations, challenges, and potential ethical considerations. Additionally, we examine the evolving frontiers of conversational AI in healthcare, providing insights into prospects and avenues for further research. This exploration aims to showcase the current state of ChatGPT in healthcare and guide future developments in using conversational AI to improve patient outcomes and overall healthcare delivery. Further, to fully harness the benefits while minimizing the risks of ChatGPT in healthcare, it is essential for policymakers, healthcare organizations, and researchers to carefully evaluate the necessary ethical and regulatory frameworks. This paper serves as a foundation for future research and development by providing valuable insights into the advantages, disadvantages, opportunities, and risks of integrating ChatGPT into healthcare. By effectively utilizing conversational AI, we can improve patient outcomes and enhance overall healthcare services by improving patient care, expediting administrative duties and promoting accessibility.